Influence of sodium replacement on fluid ingestion following exercise-induced dehydration - Wemple, R. D.; Morocco, T. S.; Mack, G. W. (International Journal of Sport Nutrition and Exercise Metabolism, 1997)
When it comes to the sodium content of a sports drink - not too much, not too little is the key. Research indicates that certain amounts of sodium added to a flavored beverage will increase voluntary drinking and help prevent dehydration.